A biomechanical model for the relation between bite force and mandibular opening angle in arthropods - Richard Johnston (Royal Society Open Science, 2023)
Bite forces play a key role in animal ecology: they affect mating behaviour, fighting success, and the ability to feed. Although feeding habits of arthropods have an enormous ecological and economical impact, we lack fundamental knowledge on how the morphology and physiology of their bite apparatus controls bite performance and its variation with mandible gape. To address this gap, we derived a comprehensive biomechanical model that characterises the relationship between bite force and mandibular opening angle from first principles. We validate the model by comparing its geometric predictions with morphological measurements on CT-scans of Atta cephalotes leaf-cutter ants. We then demonstrate its deductive and inductive power with three exemplary use cases: First, we extract the physiological properties of the leaf-cutter ant mandible closer muscle from in-vivo bite force measurements. Second, we show that leaf-cutter ants are extremely specialised for biting: they generate maximum bite forces equivalent to about 2600 times their body weight. Third, we discuss the relative importance of morphology and physiology in determining the magnitude and variation of bite force. We hope that our work will facilitate future comparative studies on the insect bite apparatus, and advance our knowledge of the behaviour, ecology and evolution of arthropods.